On the elasticity, adhesion, and friction of PDMS at the nanometer scale - Lee, W. J.; Ha, J. W.; Kim, J. M.; Caron, A. (Frontiers in Coatings, Dyes and Interface Engineering, 2024)
We apply atomic force microscopy (AFM)-based methods to quantify PDMS's elastic and tribological properties in single asperity contacts (quasi-static and sliding) with a nanometer-scale SiOx asperity under dry conditions. The selected experimental approach allows us to model the contact initiation with PDMS and its degradation. Combining quasi-static and reciprocal sliding experiments, we identify several contributions to adhesion and friction: junction formation, elastic deformation, rupture, and adhesive material transfer. Furthermore, we find correlations between the elastic deformation of PDMS/SiO2 junctions and their adhesion hysteresis on the one hand and the shear strength and the work of adhesion on the other.